Conserved phosphorylation hotspots in eukaryotic protein domain families - Marta J. Strumillo (Nature Portfolio, 2019)
Protein phosphorylation has various regulatory functions. Here, the authors map 241 phosphorylation hotspot regions across 40 eukaryotic species, showing that they are enriched at interfaces and near catalytic residues, and enable the discovery of functionally important phospho-sites.